The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1161/circinterventions.121.011387
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes After Fractional Flow Reserve–Based Deferral of Revascularization in Chronic Coronary Syndrome: Final Results From the J-CONFIRM Registry

Abstract: Background: Little large-scale data is available about the long-term (beyond 3 years) clinical outcomes after fractional flow reserve (FFR)–based deferral of revascularization in clinical practice. We sought to assess the 5-year outcomes after deferral of revascularization based on FFR. Methods: The J-CONFIRM registry (Long-Term Outcomes of Japanese Patients With Deferral of Coronary Intervention Based on Fractional Flow Reserve in Multicenter Registry)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The J-CONFIRM registry (long-term outcomes of Japanese patients with deferral of coronary intervention based on fractional flow reserve in a multicenter registry) enrolled 1,263 consecutive patients with angiographically intermediate coronary lesions and deferred revascularization after FFR assessment in 28 Japanese centers between 2013 and 2015. 8 In this registry, the 5-year cumulative incidences of cardiac death and target vessel-related myocardial infarction (TVMI) were only 1.9% and 0.95%, respectively, confirming the long-term safety of deferral of coronary revascularization based on FFR. 8 In this issue of the Journal, Ueki et al 9 report the outcomes of elderly patients after deferral of coronary revascularization in the J-CONFIRM registry.…”
Section: Shiomi Hmentioning
confidence: 73%
See 1 more Smart Citation
“…The J-CONFIRM registry (long-term outcomes of Japanese patients with deferral of coronary intervention based on fractional flow reserve in a multicenter registry) enrolled 1,263 consecutive patients with angiographically intermediate coronary lesions and deferred revascularization after FFR assessment in 28 Japanese centers between 2013 and 2015. 8 In this registry, the 5-year cumulative incidences of cardiac death and target vessel-related myocardial infarction (TVMI) were only 1.9% and 0.95%, respectively, confirming the long-term safety of deferral of coronary revascularization based on FFR. 8 In this issue of the Journal, Ueki et al 9 report the outcomes of elderly patients after deferral of coronary revascularization in the J-CONFIRM registry.…”
Section: Shiomi Hmentioning
confidence: 73%
“…8 In this registry, the 5-year cumulative incidences of cardiac death and target vessel-related myocardial infarction (TVMI) were only 1.9% and 0.95%, respectively, confirming the long-term safety of deferral of coronary revascularization based on FFR. 8 In this issue of the Journal, Ueki et al 9 report the outcomes of elderly patients after deferral of coronary revascularization in the J-CONFIRM registry. The 5-year cumulative incidence of the primary endpoint of target vessel failure was 14.3% in elderly (aged ≥75 years) patients and 10.8% in younger patients (aged <75 years) (P=0.12).…”
Section: Shiomi Hmentioning
confidence: 73%
“…Whereas prospective randomized data on the superiority of physiology-guided non-culprit vessel PCI in patients presenting with STEMI is lacking, data derived from important registries showed low event rates in vessels with a negative FFR and no subsequent revascularization in patients presenting with stable or unstable angina, supporting a conservative approach. [16,17] A meta-analysis of large national FFR registries extrapolated these findings to patients presenting with acute coronary syndrome (ACS) by demonstrating that FFR-based deferral to medical treatment was as safe as in patients with non-ACS (major cardiovascular event, 8.0% vs. 8.5%, p = 0.83; revascularization, 3.8% vs. 5.9%, p = 0.24; and freedom from angina, 93.6% vs. 90.2%, p = 0.35). [18] Also in the present study, event rates related to lesions with a vFFR >0.80 were low irrespective of subsequent revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Cox regression analysis was performed to evaluate the prognostic signifi-of coronary intervention based on fractional flow reserve in multicenter registry) has reported the low incidence of target vessel failure (TVF) after deferral of revascularization based on FFR among patients with chronic coronary syndrome (CCS), highlighting the safety of FFR-based deferral of revascularization in real-world practice. 6,7 Elderly patients are more dominant in the CCS population and often present with atypical symptoms than younger patients; therefore, assessing myocardial ischemia should be encouraged in elderly patients. Previous studies have consistently demonstrated that elderly patients have higher FFR values than younger patients despite a similar degree of coronary stenosis 8-10 due to several potential mechanisms, such as a loss of functional cardiomyocytes, microvascular dysfunction resulting from long-standing hypertension and diastolic dysfunction, 11,12 and a decreased response to vasodilator drugs.…”
Section: Discussionmentioning
confidence: 99%